Ecofeminism as a Movement: Choosing between Economics and Nature Protection - HAJAD, Vellayati; IKHSAN, Ikhsan (Theoretical and Practical Research in Economic Fields, 2024)
This research aims to discuss the direction of the ecofeminist movement in Indonesia after the New Order. The world ecofeminist movement is often criticized because it is considered to obscure the essential spirit of feminism in its efforts to protect nature. However, in Indonesia, it is widely praised for its success in protecting wildlife from potential damage. This research uses ecofeminism theory and resource mobilization theory to examine the side of women's struggle to preserve nature. In order to identify research gaps and uncharted region for further investigation, this study employed a Systematic Literature Review (SLR). There are three stages involved in SLR: planning, conducting, and reporting. The results of this research are that there is strengthening within the organization of the ecofeminist movement when natural disasters and other potential natural damage occur, thus giving rise to collective awareness about the importance of women participating in protecting nature. This research concludes that the ecofeminist movement opens up new political opportunities for women to be empowered and prosperous and protect wildlife.